Neurotherapeutic effects of novel HO‐1 inhibitors in vitro and in a transgenic mouse model of Alzheimer's disease. (6th September 2014) - Gupta, Ajay; Lacoste, Baptiste; Pistel, Paul J.; Ingram, Donald K.; Hamel, Edith; Alaoui‐Jamali, Moulay A.; Szarek, Walter A.; Vlahakis, Jason Z.; Jie, Su; Song, Wei; Schipper, Hyman M.
Abstract Heme oxygenase‐1 (HO‐1) encoded by the HMOX1 gene is a 32‐kDa stress protein that catabolizes heme to biliverdin, free iron, and carbon monoxide (CO). Glial HO‐1 is over‐expressed in the CNS of subjects with Alzheimer's disease (AD), Parkinson's disease (PD), and multiple sclerosis (MS). The HMOX1 gene is exquisitely sensitive to oxidative stress and is induced in brain and other tissues in various models of disease and trauma. Induction of the glial HMOX1 gene may lead to pathological brain iron deposition, intracellular oxidative damage, and bioenergetic failure in AD and other human CNS disorders such as PD and MS. Therefore, targeted suppression of glial HO‐1 hyperactivity may prove to be a rational and effective therapeutic intervention in AD and related neurodegenerative disorders. In this study, we report the effects of QC‐47, QC‐56, and OB‐28, novel azole‐based competitive and reversible inhibitors of HO‐1, on oxidative damage to whole‐cell and mitochondrial compartments in rat astrocytes transfected with the HMOX1 gene. We also report the effect of OB‐28 on the behavior and neuropathology of APPswe/PS1∆E9 mice. OB‐28 was found to reduce oxidative damage to whole‐cell and mitochondrial compartments in rat astrocytes transfected with the HMOX1 gene. Moreover, OB‐28 was found to significantly counter behavioral deficits and neuropathological alterations in APPswe/PS1∆E9 mice. Attenuation of AD‐associated behavioral deficits and neuropathological changes suggests that HO‐1 may be a promising target for neuroprotective intervention in AD and other neurodegenerative diseases. <boxed-text content-type="graphic" id="jnc12927-blkfxd-0100" position="anchor" orientation="portrait"> </boxed-text> We propose that the targeted suppression of glial heme oxygenase‐1 (HO‐1) hyperactivity may prove to be a rational and effective therapeutic intervention in Alzheimer's disease (AD) and related neurodegenerative disorders. We report attenuation by a selective HO‐1 inhibitor of oxidative damage to whole‐cell and mitochondrial compartments in astrocytes in vitro and amelioration of behavioral anomalies in a transgenic mouse model of AD.